Physical layer security of modify-and-forward cooperative D2D networks based on transmit antenna selection - LIU Huizhi; LI Guangqiu; ZHANG Yajuan; YE Mingzhu; GAO Hui (Dianxin kexue)
To further improve the physical layer security (PLS) performance of decode-and-forward (DF) cooperative device-to-device (D2D) network that shared spectrum resources with cellular network, a modify-and-forward (MF) cooperative D2D-cellular PLS model was proposed which the D2D transmitter adopted transmit antenna selection (TAS). The D2D transmitter equipped with multiple transmit antennas which adopted TAS technology, then the antenna with the maximum signal-to-interference-plus-noise ratio between the D2D transmitter and MF relay link was selected to send signal. The relay used MF protocol to modify the decoded legal information before forwarding, to avoid passive eavesdropper decoding the legitimate information sent at this stage, which improved the PLS performance of D2D network. The analytical expressions of secrecy outage probability, probability of non-zero secrecy capacity and asymptotic secrecy outage probability of MF cooperative D2D network were derived, and the PLS performance of DF cooperative D2D network was compared and analyzed. The numerical and simulation results show that the PLS performance of MF cooperative D2D network is better than that of DF cooperative D2D network. The PLS performance of D2D network can be enhanced by increasing the number of transmit antennas at the D2D transmitter.